Green Economy as the Instrument of Providing Sustainable Finances in the EU - M. V. Chkhan (Vestnik MGIMO-Universiteta)
Book review: Busch D., Ferrarini G., Grünewald S. 2021. Sustainable Finance in Europe. Corporate Governance, Financial Stability and Financial Markets. Springer. 511 p. DOI: 10.1007/978- 3-030-71834-3